(untitled) (Archive of Conferences, 2021)
The article scientifically analyzes the role of the clan heritage in the formation of innovative abilities of the younger generation. Abu Nasr al-Farabi warns people against bad habits such as laziness, idleness, ignorance, ignorance, unprofessionalism, etc. Abu Raikhan Beruni prioritizes free creativity and a high level of knowledge in shaping the innovative abilities of young people.